ANALISIS DAN PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN - Sahay, Abertun Sagit; Gunawan, Vincentius Abdi; Sahay, Nugraha Sagit (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Library is a service unit that provides convenience to any academic community to gainresources and activities related to the learning process . The services provided should give a goodresponse time so that services can be provided by focusing on aspects of customer satisfaction inthis academic community .Palangkaraya Christian University as one of the universities that want to implement aninformation system in managing the library collection , which is capable of providing the bestservice in the process of borrowing and returning book. By applying this library informationsystems , management expected of members, books and other collections may be better so that theprojection koleksipun updates can be done easily .This study uses the waterfall method where thestage used in this study is limited to the design stage of the six stages in this method . Stages of theanalysis carried out by processing requirements of the system . In the design phase of systemdesign , database design , interface design and drafting reports . The results of this study is a draftdocument the results of the analysis and design of the library system which has been fulfilling theneeds of the organization and user aspects.